In ∆ABC, AB = AC.
BE & CF are altitudes.
Prove that BE = CF.
Attachments:
![](https://hi-static.z-dn.net/files/d00/8e4042f0246e302fa8c73561803d9ba9.jpg)
Answers
Answered by
2
In ∆ABE &∆ ACF, AB=AC. (Given) Angle BAE= Angle CAF (common). Angle AEB=Angle AFC =90°. ∆ABE~∆ACF (AAS) BE=CF (CPCT) Hence proved.
Answered by
4
In triangle ABE and triangle ACF,
AB = AC (given)
angle AEB = angle AFC (altitudes)
angle A = angle A (common)
Therefore triangle ABE ≅ triangle ACF (AAS rule)
From this,
BE = CF (CPCT)
Similar questions
English,
8 months ago
Physics,
8 months ago
English,
1 year ago
Political Science,
1 year ago
World Languages,
1 year ago